REDESIGNING ORGANIZATIONAL STRUCTURE AS A RESPOND TO THE UNCERTAINTY ENVIRONMENT IN THE NEWSPAPER COMPANY - Muhammad Ridwan Arif; Asty Almaida (Hasanuddin Economics and Business Review, 2018)
The objective of this paper is to identify the contingency factors in respond to environmental changing in designing the organizational structure for newspaper company. The current environment exist as the industry faces an uncertain future because of stagnant markets, increasing competition from other media for audience and attention, use by progressively smaller portions of the populations, and changes in advertiser media choice. Based on the literature review, by employing the contingency perspectives,Â  the organizational size, effective strategy, and adoption the high technology will influence the capability of organization to respond the environmental changing that in turn can strengthening itâ€™s competitive advantage and innovation in uncertainty environment.